PENGARUH KEPEMIMPINAN ETIS, KEPEMIMPINAN TRANSFORMASIONAL, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI: STUDI KORELASIONAL PADA PEGAWAI KABUPATEN LEBAK - Sutisna, Ade Jaya; Nuradhani, Dadan; Rudiyanto, Rudiyanto (The Asia Pacific Journal Of Management Studies, 2023)
Our study examines the effect of ethical leadership, transformational leadership, and job satisfaction on organizational commitment. Quantitative, cross-sectional, and questionnaire methods administered to ninety employees of the Lebak Regency in Banten as data in this study. The discussion is based on data processing which analyzed by multiple regression both partially and simultaneously to obtain a significant predictor of organizational commitment. We obtained several findings including that ethical leadership has a positive effect on organizational commitment, transformational leadership has a partial positive-effect on organizational commitment, job satisfaction has a partial positive-effect on organizational commitment, and simultaneously a positive influence on ethical leadership, transformational leadership, and job satisfaction towards the organization commitment. The contribution of this research adds to the literature and proves that the intended study will be important for other district organizations in Indonesia.